(untitled) (Modern education and development, 2025)
This article explores the grammatical and semantic features of state-expressing words in the Uzbek language. These linguistic units are crucial for expressing the emotional, physical, psychological, and situational states of subjects. The study examines their morphological structures, syntactic behaviors, semantic classifications, and discursive functions. Through linguistic analysis and examples from modern Uzbek usage, the paper demonstrates how state-expressing words contribute to the expressive richness and communicative precision of the language. Additionally, parallels with related Turkic and Indo-European languages are briefly discussed to contextualize their unique and universal traits.